Comparison of Methods for Determining the Intensity of Water Erosion on Agricultural Lands in the Dry Steppe Zone of Northern Kazakhstan - Zhanzakov, Bakhtiyar; Lisenovich, Aleksandr; Kaliaskar, Dauren; Kulyntai, Fariza; Shupanova, Irina (AGRIVITA Journal of Agricultural Science, 2026)
Soil degradation due to water erosion in arable land is a common threat to soil fertility and sustainable food production. Therefore, an accurate assessment of soil water erosion is crucial. The conventional Sobolev method for assessing water erosion shows consistent data over decades of soil erosion monitoring, which may underestimate the current impact of water erosion on soil in the dry steppe zone of northern Kazakhstan. In this study, five methods for estimating land cover loss were evaluated: Sobolev, geometric cross-sectional area calculation, photogrammetry, LiDAR surveying, and satellite imagery. The LiDAR surveying showed the greatest accuracy compared with Sobolev, with total channel volumes of 84.54 m3 and 33.21 m3, respectively. The findings of this study indicate that existing official soil erosion survey data, due to the low precision of conventional field-based and manual measurement techniques, underestimate the extent of water erosion in the steppe zone of northern Kazakhstan. These results highlight the importance of integrating advanced remote sensing and geospatial methods to monitor soil water erosion in croplands in the dryland steppe zone.